2001
DOI: 10.1016/s0304-3959(00)00449-8
|View full text |Cite
|
Sign up to set email alerts
|

A randomized comparison of group cognitive–behavioral therapy, surface electromyographic biofeedback, and vestibulectomy in the treatment of dyspareunia resulting from vulvar vestibulitis

Abstract: This study compared group cognitive-behavioral therapy (12-week trial), surface electromyographic biofeedback (12-week trial), and vestibulectomy in the treatment of dyspareunia resulting from vulvar vestibulitis. Subjects were 78 women randomly assigned to one of three treatment conditions and assessed at pretreatment, posttreatment and 6-month follow-up via gynecological examinations, structured interviews and standard questionnaires pertaining to pain (Pain Rating Index and Sensory scale of the McGill Pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
353
3
9

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 428 publications
(384 citation statements)
references
References 19 publications
19
353
3
9
Order By: Relevance
“…Partner attributions about the women's pain were measured with the Extended Attributional Style Questionnaire 3,12,27,40 , adapted for use with partners of women experiencing pain during intercourse. The partner version has been used in a previous sample of PVD couples, but has not been properly validated 20 .…”
Section: Pain Attributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Partner attributions about the women's pain were measured with the Extended Attributional Style Questionnaire 3,12,27,40 , adapted for use with partners of women experiencing pain during intercourse. The partner version has been used in a previous sample of PVD couples, but has not been properly validated 20 .…”
Section: Pain Attributionsmentioning
confidence: 99%
“…This could indicate changes in partners' ability or desire to respond in positive ways as time goes on, suggesting that positive behavioral responding may take more self-regulation. One study showed that partner catastrophizing and self-efficacy partially mediated the association between higher partner solicitous responses and higher pain during intercourse in women with PVD, although only pain catastrophizing was a unique mediator 3,32 .…”
Section: Introductionmentioning
confidence: 99%
“…pain occurred after successful unpainful intercourse) subtypes were included in the study. In order to confirm the PVD diagnosis, all women underwent a medical history interview and a physical examination including a standardized pelvic examination performed by a gynecologist of our team [18]. This evaluation followed the diagnostic criteria defined by Friedrich [2] and more recently modified by Bergeron et al [30]: 1) pain in the vestibule following touch or an attempted vaginal penetration; 2) acute pain during the cotton-swab test which consists in applying pressure following a random order to the vulvar vestibule.…”
Section: Participantsmentioning
confidence: 99%
“…This intervention is judged highly effective by vulvodynia specialists [15] and is listed as a first-line treatment for vulvodynia in clinical guidelines [16] and [17]. Individual physiotherapy modalities have been shown to reduce pain significantly in women with PVD [18], [19] and [20]. A randomized controlled trial (RCT) showed a 35% pain reduction during intercourse following PFM biofeedback [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation